149k views
3 votes
2/3 + y − 1/9 = 7/9

y=?

User Eesh
by
5.0k points

2 Answers

5 votes

Question:

2/3 + y - 1/9 = 7/9

y = ?

Solution:

Find A Common Denominator For 2/3 Which Is 6/9

6/9 + 2/9 = 8/9

8/9 - 1/9 = 7/9

6/9 + 2/9 - 1/9 = 7/9

Final Answer:

y = 2/9

Hope This Helps!

-EliteAnswers-


User Ashok Poudel
by
5.7k points
4 votes

Firstly, we have to find the LCD, or lowest common denominator, of 1/9 and 2/3. We can find this by listing all the multiples of 9 and 3. In this case, the LCM is 9. Multiply 1/9 by 1/1 and 2/3 by 3/3:


(2)/(3) * (3)/(3)=(6)/(9)\\\\(1)/(9)*(1)/(1)=(1)/(9)\\\\ (6)/(9)+y-(1)/(9)=(7)/(9)

Now subtract 1/9 from 6/9:
(5)/(9) +y=(7)/(9)

Now subtract 5/9 from 7/9 and your answer will be
y=(2)/(9)

User Babak Naffas
by
5.4k points